2021
DOI: 10.1159/000518662
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Magnetic Resonance Imaging-Guided Focused Ultrasound Thalamotomy for Essential Tremor

Abstract: <b><i>Introduction:</i></b> Essential tremor is the most common movement disorder in adults. Bilateral symptoms are typical; however, bilateral thalamotomy for essential tremor is associated with a high probability of adverse events. We retrospectively investigated the efficacy and safety of staged bilateral ventral intermediate nucleus thalamotomy for refractory essential tremor using magnetic resonance imaging-guided focused ultrasound. <b><i>Methods:</i></b> W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Since publication of the landmark randomized controlled trial (RCT) demonstrating the safety and efficacy of MRgFUS thalamotomy in unilateral Essential Tremor (ET) (1), reports from several centers have documented sustained benefit from the procedure at long term follow-up (2)(3)(4)(5). Recent publications have attempted to identify key factors that may improve clinical outcomes following MRgFUS thalamotomy (4,(6)(7)(8)(9). Skull Density Ratio (SDR), lesion location and lesion volume have all been reported as important factors that determine tremor outcomes and the adverse event profile (7,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since publication of the landmark randomized controlled trial (RCT) demonstrating the safety and efficacy of MRgFUS thalamotomy in unilateral Essential Tremor (ET) (1), reports from several centers have documented sustained benefit from the procedure at long term follow-up (2)(3)(4)(5). Recent publications have attempted to identify key factors that may improve clinical outcomes following MRgFUS thalamotomy (4,(6)(7)(8)(9). Skull Density Ratio (SDR), lesion location and lesion volume have all been reported as important factors that determine tremor outcomes and the adverse event profile (7,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…SDR has also been reported as a key factor in achieving therapeutic temperature at target site (8). Despite several publications reporting outcomes following MRgFUS, the current literature is limited by small sample size, heterogeneity in institutional protocols and studies involving multiple surgeons (2)(3)(4)6).…”
Section: Introductionmentioning
confidence: 99%
“…The recent publications by Martínez‐Fernández et al, 1 Iorio‐Morin et al, 2 and Fukutome et al 3 reported encouraging results after staged bilateral MRgHiFUS thalamotomy in essential tremor patients. These observations indicate that staged bilateral ablations with MRgHiFUS might be possible and safe.…”
Section: Discussionmentioning
confidence: 95%
“…However, majority of the available data for bilateral thalamotomy were published from the 1960s to 1980s when MRI and CT were not generally available to plan and confirm the ablative targets. Recent studies of bilateral thalamotomy indicated that dysarthria was mild or transient (19)(20)(21)(22)(23)(24). Nevertheless, the second thalamotomy should be carefully considered, and for a safe second thalamotomy, it is recommended to verify the absence of adverse events associated with the first thalamotomy, keep the longest possible interval between the first and second surgery (at least 12 moths), include patients aged less than 70 years, and ensure the smallest possible lesion volume.…”
Section: Discussionmentioning
confidence: 99%